Recent advances in the understanding and management of hepatorenal syndrome - Simbrunner, Benedikt (Fac Rev, 2021)
Renal dysfunction occurs frequently in hospitalized patients with advanced chronic liver disease (ACLD)/cirrhosis and has profound prognostic implications. In ACLD patients with ascites, hepatorenal syndrome (HRS) may result from circulatory dysfunction that leads to reduced kidney perfusion and glomerular filtration rate (in the absence of structural kidney damage). The traditional subclassification of HRS has recently been replaced by acute kidney injury (AKI) type of HRS (HRS-AKI) and non-AKI type of HRS (HRS-NAKI), replacing the terms “HRS type 1” and “HRS type 2”, respectively. Importantly, the concept of absolute serum creatinine (sCr) cutoffs for diagnosing HRS was partly abandoned and short term sCr dynamics now may suffice for AKI diagnosis, which facilitates early treatment initiation that may prevent the progression to HRS-AKI or increase the chances of AKI/HRS-AKI reversal. Recent randomized controlled trials have established (a) the efficacy of (long-term) albumin in the prevention of complications of ascites (including HRS-AKI), (b) the benefits of transjugular intrahepatic portosystemic shunt placement in patients with recurrent ascites, and (c) the superiority of terlipressin over noradrenaline for the treatment of HRS-AKI in the context of acute-on-chronic liver failure. This review article aims to summarize recent advances in the understanding and management of HRS.